Regional Collaboration for Aircraft Accident Investigation as Impetus for Aviation Safety in Africa - Adediran, Adejoke (South African Yearbook of International Law)
Aircraft accident investigation is a feedback mechanism which enhances aviation safety by identifying inadequacies and also taking steps to prevent future accidents. Investigation in this regard is to be carried out by International Civil Aviation Organisation (ICAO) states through national accident investigation authorities and should there be a lack of human or economic resources, regional accident investigation organisations can be formed by states to benefit from a balance on economies of scale. This article examines regional collaboration for aircraft accident investigation in Africa. It finds that the performance of African States in the area of aircraft accident investigation is below average and also notes that a major cause of this inadequacy is a lack of both human and economic resources. It thereby posits that regional collaborations on aircraft accident investigation among African states will advance aviation safety in Africa, and it is thus necessary for African states to collaborate on this. While acknowledging the contributions of the Banjul Accord Group Accident Investigation Agency, a case is made for the establishment of regional aircraft accident investigation organisations in Africa on a wider scale through the existing regional economic communities recognised by the African Union.